Lenalidomide: safety and clinical benefit†. Issue 2 (12th March 2012) - Olmo, M.; Martínez, M.; Castelló, A.; Ahmad, F.; Mangues, I.; Schoenenberger, J.A.
Abstract : Background: With the adoption of electronic medical records in our hospital, it became easier to conduct medicines use studies. Purpose: Aim of the study: To describe the safety and clinical benefit that lenalidomide treatment yielded in our patients. Materials and methods: An observational and retrospective study was conducted including patients who received lenalidomide for multiple myeloma (MM) (authorised indication) or myelodysplastic syndrome with 5q deletion (MDS5q-) (off-label use). Patients were identified from the pharmacy's electronic register. The variables were: demographics, diagnosis, duration of response, reason for stopping treatment, transfusion requirements (MDS), and incidence of adverse drug events. Results: A total of 20 patients entered the study (11 men and 9 women): 16 affected with MM and 4 with MDS. MM patients began at the standard dose of 25 mg/day and MDS at 10 mg/day. Of all, 6 (30%) required dose reduction during treatment (4 MM and 2 SMD), and the main reason for it was toxicity. Among patients with MM, 4 (25%) stopped treatment because of progression, another 4 (25%) died and 1 (6%) underwent transplantation. Among patients with MDS, 2 patients discontinued: one died and another evolved to acute myeloid leukaemia. 13 out of 20 (65%) experienced toxicity, 5 (25%) haematological, 4 (20%) respiratory infection, 2 (10%) diarrhoea and 2 (10%) renal failure. None of the patients with MDS 5q- required blood transfusions during treatment. The mean duration of response of patients who completed treatment was 13 months (range: 1-41). For patients who are still on treatment the mean duration is 15 months (range: 3-29). Conclusions: Lenalidomide offers good clinical results due to the average duration of response. Our case series has showed frequent and severe toxicity that has led to dose reductions or even patient death. Therefore, the limiting factor for lenalidomide therapy is its toxicity and consequently close safety monitoring is mandatory.